Comparison between Laparoscopic Hysterectomy and Abdominal Hysterectomy - Shrestha, R; Yu, LH (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: Hysterectomy can be performed by abdominal, vaginal and laparoscopic methods. Laparoscopic hysterectomy has been reported as an alternative to traditional abdominal hysterectomy with benefit of early recovery, short hospital stay and less operative complications. This study compared laparoscopic versus abdominal hysterectomy in terms of surgery time, blood loss, post-operative recovery, and duration of hospital stay. Methods: This is a retrospective comparative study among sixty patients who underwent laparoscopic or abdominal hysterectomy for various indications in the Department of Obstetrics and Gynaecology of the Third affiliated hospital of Zhengzhou University from January to March 2007. The data of the patients meeting the set criteria were obtained from the hospital records and hospital based computerized coding system. Enrolled cases were divided in two groups with thirty in each arm. Group TLH (total laparoscopic hysterectomy) was designated for patients who underwent total laparoscopic hysterectomy and group TAH (total abdominal hysterectomy) for those who underwent total abdominal hysterectomy. Results: There was comparatively less blood loss in TLH group (60.2±5.17 ml versus 75.7±7.12 ml) but it was statistically insignificant (p=0.12). The laparoscopic hysterectomy took longer time (107.6±32.4 min versus 74.9±31.1 min) than the abdominal (p<0.001). There was early recovery among TLH group 1.6±0.6 days versus 2.1±0.5 days in TAH group (p=0.001). Mean duration of hospital stay was significantly shorter in TLH group 7.6±1.9 days versus 10.1±2.1 days in TAH group (p<0.001). Conclusions: Laparoscopic hyserectomy is an effective alternative to abdominal hysterectomy with the advantage of less intra-operative blood loss, fast recovery and short hospital stay. DOI: http://dx.doi.org/10.3126/njog.v9i1.11183 NJOG 2014 Jan-Jun; 2(1):26-28